2016
DOI: 10.1155/2016/1057878
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spectral Characteristics of Pure Moxa Stick Burning by Hyperspectral Imaging and Fourier Transform Infrared Spectroscopy

Abstract: The objective of this study was to investigate the spectra characteristics (SC) at wavelengths of 400~1000 nm and 2.5~15.5 μm of pure moxa stick (MS) during its 25-minute burning process using new spectral imaging techniques. Spectral images were collected for the burning pure MS at 5, 10, 15, 20, and 25 min using hyperspectral imaging (HSI) and Fourier transform infrared spectroscopy (FTIR) for the first time. The results showed that, at wavelengths of 400~1000 nm, the spectral range of the cross section of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Furthermore, the chemical functional groups of CMZ were characterized via Fourier transform infrared spectroscopy (FTIR) spectra. Specifically, CMZ contained typical absorption peaks at 3447, 2920, and 1110 cm –1 , corresponding to hydroxyl, hydrocarbon and ether bonds respectively, which was consistent with the description in the literature (Figure d) . The band structure determines the optical absorption performance of the material .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the chemical functional groups of CMZ were characterized via Fourier transform infrared spectroscopy (FTIR) spectra. Specifically, CMZ contained typical absorption peaks at 3447, 2920, and 1110 cm –1 , corresponding to hydroxyl, hydrocarbon and ether bonds respectively, which was consistent with the description in the literature (Figure d) . The band structure determines the optical absorption performance of the material .…”
Section: Resultssupporting
confidence: 86%
“…Specifically, CMZ contained typical absorption peaks at 3447, 2920, and 1110 cm −1 , corresponding to hydroxyl, hydrocarbon and ether bonds respectively, which was consistent with the description in the literature (Figure 1d). 20 The band structure determines the optical absorption performance of the material. 21 Compared with ZnO (2.80 eV), CMZ had a narrower bandgap of about 2.00 eV, indicating that the addition of CM (1.25 eV) was beneficial for reducing the bandgap (Figures 1e and S3b).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the peak value is 0.8∼5.6 m. Some researchers believe that moxibustion can produce infrared radiation energy that penetrates the skin, reaches the muscle tissue, and resonates with human acupoints, which may be one of the mechanisms of moxibustion. Therefore, attention should be paid to the spectral range of the light effect and the mechanism of wave peak in the treatment of dysmenorrhea to provide the experimental basis for the target of moxibustion in the treatment of PD [ 99 , 100 ].…”
Section: The Mechanism Of Moxibustionmentioning
confidence: 99%
“…S-Moxi could effectively increase the plasma LDL/VLDL and 3-HB levels, while decreasing the plasma valine level, indicating its beneficial effect on lipids metabolism and endothelial injury repair. Previous studies have demonstrated S-Moxi could ameliorate hepatic metabolism and promote blood circulation [ 46 , 47 ]. Taken together, we speculate the main acting sites of S-Moxi may be the liver and vasculature.…”
Section: Discussionmentioning
confidence: 99%